Brominated Graphene as Mimetic Peroxidase for Sulfide Ion Recognition - Singh S.; Mitra K.; Shukla A.; Singh R.; Gundampati R.K.; Misra N.; Maiti P.; Ray B. (My University, 2025)
Brominated graphene (GBR) with ∼3% bromine content has shown novel peroxidase mimetic activity toward 3,3′,5,5′-tetramethylbenzidine (TMB) in the presence of H2O2. Optimum activity has been observed at pH 4.48 and after a minimum ∼30 min of equilibration time. Among the different analytes studied using the sensor combining TMB, H2O2, and GBR in phosphate buffer of pH 4.48, the S2- ion has effectively shown a short duration of sensing (∼2 min) within the detection range of 0.04-1 mM. A calibration curve for S2- ion estimation has been constructed with the experimental linearity in 0.04-0.4 mM range and having the limit of detection (LOD) value of 25.3 μM. A standard addition experiment has validated the method. A paper strip sensor has been fabricated for successful detection of S2- ion. © 2016 American Chemical Society.